2015
DOI: 10.5194/acp-15-2387-2015
|View full text |Cite
|
Sign up to set email alerts
|

Simulating aerosol–radiation–cloud feedbacks on meteorology and air quality over eastern China under severe haze conditionsin winter

Abstract: Abstract. The aerosol-radiation-cloud feedbacks on meteorology and air quality over eastern China under severe winter haze conditions in January 2013 are simulated using the fully coupled online Weather Research and Forecasting/Chemistry (WRF-Chem) model. Three simulation scenarios including different aerosol configurations are undertaken to distinguish the aerosol's radiative (direct and semi-direct) and indirect effects. Simulated spatial and temporal variations of PM 2.5 are generally consistent with surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 57 publications
3
84
2
Order By: Relevance
“…Péré et al (2014) and Baró et al (2017a) found a reduction in the atmospheric boundary layer height and the wind speed over most of eastern Europe when the ARI were taken into account in their simulations to study the same wildfires episode. Due to these effects on meteorology, Zhang et al (2015) revealed an effect on aerosol concentrations which could explain the observed improvement of AOD over the eastern part of the domain observed herein. Regarding the determination coefficient (Fig.…”
Section: Russian Wildfires Casementioning
confidence: 57%
“…Péré et al (2014) and Baró et al (2017a) found a reduction in the atmospheric boundary layer height and the wind speed over most of eastern Europe when the ARI were taken into account in their simulations to study the same wildfires episode. Due to these effects on meteorology, Zhang et al (2015) revealed an effect on aerosol concentrations which could explain the observed improvement of AOD over the eastern part of the domain observed herein. Regarding the determination coefficient (Fig.…”
Section: Russian Wildfires Casementioning
confidence: 57%
“…S5, the polluted air parcels could typically have been processed under severe haze conditions in Beijing and in cities south of it for more than 3 days before the peak pollution hour in Beijing. Because cloud amounts were low ( 7 , 72 , 73 ) during the January 2013 winter haze periods, we assumed that aerosols spent 100% of their lifetime under noncloud conditions (RH < 100%) ( 21 ). Under these conditions, to produce the observed sulfate concentration (~200 μg m −3 ), the required average heterogeneous production rate can be determined to be ~3 μg m −3 h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies concentrated on the direct ra-E. Athanasopoulou et al: Changes in domestic heating fuel use in Greece 10599 diative effect (DRE) of aerosols and their impact on ground temperature (Vogel et al, 2009;Stanelle et al, 2010;Bangert et al, 2012;Lungren et al, 2013;Athanasopoulou et al, 2013). Severe winter haze events over the heavily polluted North China Plain and over eastern China were found to have a significant negative RF ranging from 20 to 140 W m −2 (Gao et al, 2015;Zhang et al, 2015). Focusing on a carbonaceousrich aerosol loading induced by wildfires in Greece, Athanasopoulou et al (2014) revealed a negative impact on the surface radiative budget on the order of 10 W m −2 (3-day average) and a reduction of surface temperature by 0.5 K over land.…”
Section: Introductionmentioning
confidence: 99%